Exploring Moringa Leaves on Hemoglobin Levels: An MBKM Activity by Universitas Indo Global Mandiri Student’s - Tamiah, Aisyah; Hertati, Lesi; Asharie, Asmawati (International Journal of Social Science and Community Service, 2023)
The challenges faced by young women are closely linked to their health, specifically anemia, characterized by a reduction in hemoglobin levels. Anemia is defined as a condition where the quantity of red blood cells is insufficient to meet the body's physiological needs. The management of anemia in adolescents has been planned through the use of blood supplement tablets (TTD). However, the consumption of TTD has not been maximized due to taste issues and side effects that manifest after intake. Moringa leaves (Moringa oleifera) are known to contain various nutritional elements, including iron, vitamin C, protein, vitamin A, calcium, and potassium, making them a potential alternative for anemia treatment. The iron content in Moringa leaves is 28.2 mg. This research adopts a pre-experimental design with a one-group pretest-posttest approach, involving a sample size of 24 and utilizing paired t-test analysis. A significant difference was observed in Hb levels before and after the administration of Moringa leaf extract (p < 0.05). The average value before treatment was 10.83, with a standard deviation of 0.8641, and after treatment, it increased to 12.72, with a standard deviation of 0.9399. The findings indicate that Moringa leaf extract is effective in increasing hemoglobin levels in adolescent girls.